KRAS and BRAF Mutation in Borderline Epithelial Type Ovarian Tumor - Suardi, Dodi (Indonesian Journal of Obstetrics and Gynecology, 2013)
Objective: To understand the molecular profile by identifying the mutation of KRAS and BRAF in borderline type ovarian tumor. Method: In the study, we examined paraffin tissue sample from Department of Pathology Anatomy, University of Indonesia/Dr. Cipto Mangunkususmo Hospital, Jakarta, that was diagnosed as borderline epithelial ovarian tumor. Seventeen samples were taken to Sandya Laboratory in Bandung for examination of PCR BRAF exon 15 codon 600, and KRAS in exon 2 codon 12 and 13, as well as exon 3 codon 61. Result: Mutation of KRAS occurred in 94% of subjects (serous borderline 62.5%, mucinous bordeline 37.5%), of which 70.6% mutation happened in exon 2 codon 12 (serous borderline 33.3%, mucinous borderline 66.7%), 52.9% mutation in exon 2 codon 13 (serous borderline 33.3%, mucinous borderline 66.7%), and 76.5% mutation in exon 3 codon 61 (serous borderline 30.8%, mucinous borderline 69.2%). Mutation of BRAF occurred only in 47% of subjects, but the results of Exact Fisher test showed that mutation in BRAF gave significant result, while other variables did not give significant result (p=0.009). Conclusion: Molecular pathology in borderline ovarian tumor related with BRAF mutation is more likely to occur in serous borderline type, while KRAS mutation is more likely to occur in mucinous borderline type. [Indones J Obstet Gynecol 2013; 37-2: 107-12] Keywords: borderline ovarian tumor, BRAF, KRAS